Territorial impacts of the EU Cohesion Policy in Iberian Peninsula (1990-2010) - Medeiros, E. (2021)
This article addresses the territorial impacts of the EU Cohesion Policy in Iberian Peninsula (1990-2010). It makes use of an innovated TIA tool (the TARGET_TIA) which goes beyond the typical EU dimensional TRIAD (economy + society + environment) in assessing territorial impacts, as it also values the “territorial governance” and “spatial planning” related components in this fundamental analysis. Moreover, this TIA tool allows for a multivector enquiry, by including counterfactual evaluation elements, such as the multiplier, the exogenous, and the sustainable policy effects. In the end, our analysis concluded that the territorial impacts from the EU Cohesion Policy in both Iberian countries were positive (+1.3 in a scale from -4 to +4). Notwithstanding, these impacts were more positive in Spain than in Portugal. However, the obtained “generic potential impact value” for Iberian Peninsula was far from a desired one, which showed high inefficiencies in the use of EU funds. Also, a high variation in the analysed dimensions was detected. In sum, the positive impacts were higher in the socioeconomic cohesion and the environmental sustainability dimensions, whereas the territorial governance/cooperation and morphologic polycentricity ones obtained residual positive impact values. Furthermore, at the regional level, large asymmetries were detected in these estimated impact values, as the less developed Iberian regions showed, in general, less positive results, than the more developed ones.